Efficient noble-metal-free catalysts supported by three-dimensional ordered hierarchical porous carbon - Zhou, Weiqiang (2022)
Development of heterogeneous catalysts has attracted increasing attention, owing to their remarkable catalytic performance and recyclability. Herein, we report well-developed heterogeneous catalysts with a three-dimensional ordered hierarchical structure, constructed from nickel or cobalt nanoparticles embedded in porous carbon. The obtained catalysts were fully characterized by several techniques. On account of the uniform distribution of metal nanoparticles in the porous carbon matrix and large diffusion channels that allow for effective mass transport, the catalysts exhibited superior catalytic performance for styrene epoxidation reaction. In particular, the catalysts showed good catalytic activity, high selectivity and excellent recyclability toward the styrene epoxidation. Thus, this facile approach developed allows for fabricating advanced heterogeneous catalysts with high catalytic activities for useful practical applications.